2020
DOI: 10.3389/fpubh.2020.00433
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Cardiovascular Medicines Prices in Four European Countries

Abstract: The aim of the current study was to compare pricing methodologies at the manufacturer, wholesale, and retail levels, and to estimate the price differences of AT1-receptor blockers (sartans), Angiotensin-converting enzyme (ACE)-inhibitors, and their fixed-dose combinations (FDCs) in four countries using similar methodologies: Slovakia, Greece, Bulgaria, and Romania (SK, GR, BG, and RO, respectively). The methodologies for manufacturer, wholesale, and retail price establishment have been compared using nationall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…(1) alimentary tract and metabolism (META); (2) antiinfectives for systemic use (INFEC); (3) antineoplastic and immunomodulating agents (ONCIM); (4) antiparasitic products, insecticides and repellents (PARA); (5) Blood and blood forming organs (HAEM); (6) cardiovascular system (CARD); (7) (8) genito-urinary system and sex hormones (URO); (9) musculo-skeletal system (MUSCO); (10) nervous system (NEURO); (11) respiratory system (RESP); (12) sensory organs (SENS); (13) systemic hormonal preparations, excluding sex hormones and insulins (HORM), and (14) various indications (VAR). A list of the investigated indication areas can be found with single-digit letter abbreviation and indication abbreviation in the Additional files 1 and 3.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(1) alimentary tract and metabolism (META); (2) antiinfectives for systemic use (INFEC); (3) antineoplastic and immunomodulating agents (ONCIM); (4) antiparasitic products, insecticides and repellents (PARA); (5) Blood and blood forming organs (HAEM); (6) cardiovascular system (CARD); (7) (8) genito-urinary system and sex hormones (URO); (9) musculo-skeletal system (MUSCO); (10) nervous system (NEURO); (11) respiratory system (RESP); (12) sensory organs (SENS); (13) systemic hormonal preparations, excluding sex hormones and insulins (HORM), and (14) various indications (VAR). A list of the investigated indication areas can be found with single-digit letter abbreviation and indication abbreviation in the Additional files 1 and 3.…”
Section: Methodsmentioning
confidence: 99%
“…Even for innovative drugs, such as biologics and biosimilars, reference prices have a huge costcontainment potential as well as positive prescription effects [11]. Prior research has also found that the affordability of pharmaceuticals varies through indication areas [12][13][14][15][16]. Moye-Holz and Vogler investigated the price setting of cancer drugs in 16 European and Latin American countries and showed that high-income countries report lower PPP-adjusted prices for cancer medicines than middle-income countries and therefore were more affordable [17].…”
Section: Introductionmentioning
confidence: 99%